An Ultra-Compact 28 GHz Arc-Shaped Millimeter-Wave Antenna for 5G Application - Praveen Kumar; Tanweer Ali; Om Prakash Kumar; Shweta Vincent; Pradeep Kumar; Yashwanth Nanjappa; Sameena Pathan (Micromachines, 2022)
The 5th generation (5G) network was planned to provide a fast, stable, and future-proof mobile communication network to existing society. This research presents a highly compact arc shape structure antenna resonating at 28 GHz for prospective millimeter-wave purposes in the 5G frequency spectrum. The circular monopole antenna is designed with a radius of 1.3 mm. An elliptical slot on the radiating plane aids in achieving an enhanced bandwidth resonating at the frequency of 28 GHz. Including an elliptical slot creates new resonance and helps improve the bandwidth. The antenna has an ultra-compact dimension of 5 × 3 × 1.6 mm3, which corresponds to an electrical length of 0.46λ × 0.28λ × 0.14λ, where λ is free space wavelength at the resonant frequency. The projected antenna has an impedance bandwidth of 15.73 % (25.83–30.24 GHz). The antenna has a good radiation efficiency of 89%, and the average gain is almost 4 dB over the entire impedance bandwidth. The simulated and experimental S11 findings are in good agreement.